PENDEKATAN DESAIN UNTUK PONDOK KULINER DAN PUSAT UMKM DI KAWASAN WISATA EMBUNG SOKAPANCA DESA GOGIK KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - riza susanti; Previari Umi Pramesti (Jurnal Pengabdian Vokasi, 2022)
Gogik village is one of villages in sub-district of Ungaran Barat, district of Semarang. Nowadays, Gogik village attemps to develop its nature potencies which is one of them is the area of embung Sokapanca. A design recommendation was proposed by the study programme of Civil Infrastructure Engineering and Architectural Design, Department of Civil and Planning, Vocational School, Diponegoro University, through a community service programme. The design approach used exotic, unique, and authentic as the concept. Neo-vernacular and contemporary architecture were adopted for the design of culinary hut and the centre of Small and Medium Enterprises. The concept of sustainable tourism will be implemented to maintain the harmony with the environment, nature, humanism value, and local wisdom.